Mar de lobos - Low, Robert (Low, Robert. Ira de los hombreas del norte, 2012)
Washed up in a hostile city, battle weary and out of luck, the Oathsworn lie waiting for their reluctant leader to bring them back to wealth and warfare. But Orm's prized sword is gone.